Helicobacter pylori CagA Tertiary Structure Reveals Functional Insights - Backert, Steffen; Tegtmeyer, Nicole (Cell Host & Microbe, 2012)
CagA is a major disease-associated factor injected by the gastric pathogen Helicobacter pylori. In this issue, Hayashi et al. (2012) report the crystallographic structure of the CagA N terminus (residues 24–876) at 3.19 Å resolution. This study revealed three distinct domains, giving novel insights into intramolecular and intermolecular protein and phosphatidylserine interactions.
Created from Fastlane, Scopus look-up